"Les gens qui vous ressemblent": Discursive Negotiation of Identity and Construction of Affiliation in the 2019 Canadian Federal Election Party Leader Debates. Issue 1 (1st December 2021) - Bosworth, Yulia
Abstract : In the weeks leading up to the Canadian federal election, federal party leaders seek to appeal to a crucial part of the electorate – Québec voters, most of whom are of French-Canadian background – through a series of televised debates. As party leaders engage in discourse aimed at creating proximity with and enacting an affiliative stance toward these voters, the debates become a platform for discursive negotiation of Québec identity, in which identity stances and narratives are reflected, reproduced, and challenged. This study examines a corpus of party leaders' discourse as these political actors interactively negotiate Québec identity during three party leader debates in the 2019 federal election. Following the theoretical framework of Critical Discourse Analysis, the inquiry discusses the following aspects of the party leaders' discourse: discursive representation of Quebecers' group identity and self-positioning with respect to that identity, use of symbolic lexis and references that signal attachment to the French-Canadian majority's collective memory, and self-positioning with respect to the French language. In addition, the discussion addresses implications of the bilingual nature of political discourse in the Canadian context, focusing on party leaders' use of code-switching and metapragmatic commentary. Crucially, the study's conclusions suggest that a shared vision of Québec identity has not yet been widely ratified. While the party leaders' discourse appears largely felicitous with the inclusive, civic vision of Québec identity, the study's findings point to continued primacy of the French-Canadian fact in its current conceptualization.